Introduction to Biomethane - Sirichai Koonaphapdeelert (2020)
© 2020, Springer Nature Singapore Pte Ltd. The global market of biofuels is led by bioethanol and biodiesel. Bioethanol is industrially produced from sugarcane, wheat, corn, and sugar beet. Biodiesel is made from vegetable oils and, in limited cases, from fats and waste cooking oils. In comparison, global biogas production was 27% of the global biofuel market or about 0.25% of the global energy market in 2011. Any kind of biomass has potential to be a substrate for biogas production as long as it contains carbohydrates, proteins, fats, cellulose, and hemicelluloses. Biogas is a gas formed in an anaerobic process which is the decomposition of organic matter without oxygen. Anaerobic digestion consists of four stages, namely, hydrolysis, acidogenesis, acetogenesis, and methanogenesis to break down biodegradable materials in the absence of oxygen by a consortium of microorganisms. Waste from agriculture or general household waste, manure, plants, or food waste can produce biogas. It is regarded as a renewable energy source as organic matter can be grown indefinitely. As it is produced from waste, it has advantages over other renewables that use organic non-waste as their raw material, such as certain ethanol plants, firewood, and charcoal. Biogas contains methane, which is useful, but also several gases that are not so useful such as carbon dioxide and hydrogen sulfide. Biomethane is a gas that results from a process that improves the quality of biogas by reducing the levels of carbon dioxide, hydrogen sulfide, moisture, and other gases. If these gases could be removed entirely, the biomethane that remains is pure methane. The name biomethane refers to the method of production, rather than the gas content. This chapter explains the difference between biogas and biomethane and explores the production of biomethane in selected countries.